Rancang Bangun Sistem Pengamatan Ketinggian Air dan pH Air pada Sawah dengan Komunikasi LoRa menggunakan Metode Time Divison Multiple Access (TDMA) - Irvana Alfiyan Nur; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Rice fields are one of the most important agricultural sectors for a country, because rice fields are the largest source of food for the Indonesian people. Like rice, rice is a relatively short-lived seasonal crop. Rice production itself is largely determined by plant genetics and environmental management of the land. In the process of rice farming, sufficient water and regular nitrogen fertilizers on the land are needed. Lack of understanding of most farmers in cultivating land is one of the problems in agriculture that can make crop yields less than optimal. Therefore, a monitoring system with WSN (Wireless Sensor Network) technology was created to help monitor water level and water pH, making it easier for farmers to find out the benchmark for water level and the pH value of water in their land. The system consists of 3 (three) slave nodes and 1 (one) master node which is in charge of sensing and sending data on water level and water pH. From the test results that have been done, the system can send data from the slave node to the master node using LoRa SX1276 communication. The device is capable of covering a large area with low power consumption with an RSSI signal at node 1 of -112.88 dB, node 2 of -102.76 dB, node 3 of -110.1 dB. The system is also equipped with the TDMA method, which is useful for scheduling data delivery that can reduce data collisions. The results of the sensing data will be displayed periodically on ThingSpeak.